The Formation of Customary Law Related to the Use of Natural Resources in the Lore Lindu Region - Agus Lanini; Sulbadana Sulbadana; Aminuddin Kasim; M. Yasin Nahar; Surahman Surahman (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
The research aims to know and comprehend the customary law principles as a rule in the exploration of natural resources, to know communities behavior on customary law in exploring the natural resources, and to explain the customary law as a beneficial rule to conserve the natural resources in lore lindu region. It will be conducted through the research method of socio-legal by data collecting will be done by direct observation of the research object as well as interview and participatory appraisal. Secondary data such as documented policy, law and regulations, political agreements, village demographic data, and other supporting data will be collected from various sources of concerns. The result of the research could be revealed as that the customary law principles as a rule in the explorations of natural resources still influence their rule in using its of course lead by head of tribe (totua Ngata) for a long time ago. As well as the communities behavior on customary law in using the natural resources in general. Then the customary law as a beneficial rule to conserve the natural resources in lore lindu region in particular can be assumed, but the intervention of state law or policy made it diminish gradually. Customary law related to forest conservation as a part of their values such as ombo (forbidden) cutting or bring tree or fish in a certain time. Keyword: Formation; Customary Law; Natural Resources; National Park